A Collaborative Effort to Advance Drug Development in Pediatric Constipation and Irritable Bowel Syndrome. Issue 2 (August 2021) - Saps, Miguel; Nurko, Samuel; Benninga, M.A.; Di Lorenzo, Carlo; Garza, Jose M.; Thapar, Nikhil; Richards, Kelly; Lee, Jessica J.; Altepeter, Tara
Abstract : ABSTRACT: Pediatric functional gastrointestinal disorders including irritable bowel syndrome with constipation and functional constipation are common conditions in childhood, but no drugs are U.S. Food and Drug Administration (FDA) approved for chronic use in pediatric patients with these disorders. Despite efforts to better standardize the diagnosis of these conditions in children (including recent modifications to the Rome criteria), conducting pediatric clinical trials to support drug approval remains a challenge. In March 2018, FDA, in collaboration with the North American Society for Pediatric Gastroenterology, Hepatology, and Nutrition, American Gastroenterological Association, and American College of Gastroenterology, convened a public workshop to discuss the challenges and opportunities in conducting pediatric clinical trials in functional gastrointestinal conditions. The workshop assembled gastroenterologists, psychologists, patients, patient advocates, regulators, and industry representatives to discuss trial design and conduct including alternative designs, eligibility criteria, instruments for patient- and observer-reported outcomes, and optimal primary endpoints to support regulatory approval. This report summarizes the workshop, key challenges and knowledge gaps identified, and outlines areas where further research efforts are needed to overcome barriers to developing drugs to treat these conditions.